Daniel Gordis, Menachem Begin: The Battle for Israel’s Soul, Nueva York, Schocken, 2014, 295 pp. - Joseph Hodara (El Colegio de México, A.C., 2016)
Daniel Gordis, Menachem Begin: The Battle for Israel’s Soul, Nueva York, Schocken, 2014, 295 pp.